Decreased integration of default-mode network during a working memory task in schizophrenia with severe attention deficits - Cheng, Peng; Liu, Zhening; Yang, Jun; Sun, Fuping; Fan, Zebin; Yang, Jie (Frontiers in Cellular Neuroscience, 2022)
Background: Working memory (WM) and attention deficits are both important features of schizophrenia. WM is closely related to attention, for it acted as an important characteristic in activating and manipulating WM. However, the knowledge of neural mechanisms underlying the relationship between WM and attention deficits in schizophrenia is poorly investigated. Methods: Graph theory was used to examine the network topology at the whole-brain and large-scale network levels among 125 schizophrenia patients with different severity of attention deficits (65 mild attention deficits; 46 moderate attention deficits; 14 severe attention deficits) and 53 healthy controls (HCs) during an N-back WM task. These analyses were repeated in the same participants during the resting state. Results: During the WM task, schizophrenia with severe attention deficits showed decreased integration of the default mode network (DMN) compared with schizophrenia with mild attention deficits and HCs; all patient groups showed increased small-worldness and local clustering of the whole-brain compared with HCs. However, these observations were not persisted under the resting-state. Further correlation analyses indicated that poorer accuracy of WM task was correlated with severer clinical symptoms and higher topology properties of the whole-brain and DMN. Besides, the detected topology properties were statistically associated with attention deficit level. Conclusion: Our research demonstrated that the severity of attention deficits was associated to the topology of the functional connectome during WM task among patients with schizophrenia. Schizophrenias with severe attention deficits were accompanied by decreased integration of DMN when performing the WM Task.